The Polysemic Network of the Verb Ficar in Portuguese L1 (Brazil) and Portuguese L2 (French language learners): Acquisition and Pedagogy (Revista de Estudos da Linguagem, 2024)
This paper analyzes how the different senses of the verb ficar are used in an elicitation test in Portuguese as a first and a second language (L1/L2). The aim of this study is to analyze the organization and use of the polysemic network of ficar for two groups of participants. The most prototypical meanings of a word or a construction have been operationalized in many studies as the most mentioned ones in elicitation experiments (Gries, 2015, p.473). Portuguese L1 participants were instructed to elicit three sentences with the verb ficar. On the other hand, learners of Portuguese (L2) were asked to do the same test, and also to translate their sentences into French. The translation task aimed to understand what meaning the learners intended to convey when they used the verb ficar. It also served to analyze which verbs were used by the learners to translate this verb (equivalences). The results revealed a different organization of the polysemic network of the verb ficar in Portuguese L1 and L2. L2 group elicited concrete meanings more frequently than L1 group whereas L1 participants elicited abstract meanings more frequently than L2 participants. The analysis also revealed very little variation between the results of participants with an initial level of L2 Portuguese and more advanced levels. This fact shows that it is difficult to acquire frequent and polysemous verbs in L2 and corroborates the trends observed in literature.